Is spreading prolonged, episodic or incipient in the Andaman Sea? Evidence from deepwater sedimentation - C. K. Morley (2018)
© 2014 Elsevier Ltd. The Central Andaman Basin (CAB) is generally accepted to be a site of continuous sea floor spreading since the Early Pliocene (~4.0. Ma). The adjacent Alcock and Sewell Rises, and part of the East Andaman basin have been interpreted as probable Miocene oceanic crust. Published seismic lines across the eastern half of the spreading centre show that 100's. m thickness of sediment are present right up to the central trough. The central trough margins are faulted, uplifted and tilted away from the central trough. The youngest sediment is ponded and onlaps the tilted central trough margin, while older faulted sediment lies within the trough. Such a configuration is incompatible with continuous spreading. Instead, either spreading in the central basin was episodic, probably comprising a Late Miocene-Early Pliocene phase of spreading, followed by extension accommodated in the Alcock and Sewell rise area (by faulting and dike intrusion), and then a recent (Quaternary) return to spreading in the central trough; or the central trough marks an incipient spreading centre in hyper-thinned continental (or possibly island arc) crust. To resolve these possibilities regional satellite gravity data was inverted to determine crustal type and thickness. The results indicate the CAB is oceanic crust, however the adjacent regions of the Alcock and Sewell Rises and the East Andaman Basin are extended continental crust. These regions were able to undergo extension before seafloor spreading, and when seafloor spreading ceased. Unpublished seismic reflection data across the East Andaman Basin supports the presence of continental crust under the basin that thins drastically westwards towards the spreading centre. Episodic seafloor spreading fits with GPS data onshore that indicate the differential motion of India with respect to SE Asia is accommodated on widely distributed structures that lie between the trench and the Sagaing Fault.